15N Natural Abundance Evidences a Better Use of N Sources by Late Nitrogen Application in Bread Wheat - Fuertes-Mendizábal, Teresa; Estavillo, José M.; Duñabeitia, Miren K.; Huérfano, Ximena; Castellón, Ander; González-Murua, Carmen; Aizpurua, Ana; González-Moro, María Begoña (Frontiers in Plant Science, 2018)
This work explores whether the natural abundance of N isotopes technique could be used to understand the movement of N within the plant during vegetative and grain filling phases in wheat crop (Triticum aestivum L.) under different fertilizer management strategies. We focus on the effect of splitting the same N dose through a third late amendment at flag leaf stage (GS37) under humid Mediterranean conditions, where high spring precipitations can guarantee the incorporation of the lately applied N to the soil-plant system in an efficient way. The results are discussed in the context of agronomic parameters as N content, grain yield and quality, and show that further splitting the same N dose improves the wheat quality and induces a better nitrogen use efficiency. The nitrogen isotopic natural abundance technique shows that N remobilization is a discriminating process that leads to an impoverishment in 15N of senescent leaves and grain itself. This technique also reflects the more efficient use of N resources (fertilizer and native soil-N) when plants receive a late N amendment.